Pengaruh Ukuran Perusahaan, Struktur Aktiva dan Profitabilitas terhadap Struktur Modal pada Perusahaan Farmasi Yang Terdaftar di Bursa Efek Indonesia Periode 2016-2020 - Prastyo, Dafit Januar; Listyaningsih, Erna; Indriani, Wiewiek (Universitas Malahayati, 2022)
Abstract Purpose:This study aims to determine how the effect of firm size, asset structure, profitability including Return on Assets (ROA), Return on Equity (ROE) and Net Profit Margin (NPM) on capital structure. The type of data used in this study is secondary data obtained from the official website of the Indonesia Stock Exchange. Design/ Research Method : The population in this study were all pharmaceutical companies. The samples used were 8 pharmaceutical companies. Sampling using purposive sampling technique using certain criteria. Data analysis in this study used several methods, namely descriptive statistical test, classical assumption test, multiple linear analysis, R2 Test, F test and T test. Result:The results of this study indicate that (1) company size has an effect on the capital structure of pharmaceutical companies listed on the IDX for the 2016-2020 period;; (2) Profitability affects the capital structure of pharmaceutical companies in pharmaceutical companies listed on the IDX for the 2016-2020 period, including: (a) ROA has a significant effect on capital structure, (b) NPM has a significant influence on capital structure, and ( c) ROE has a significant influence on the capital structure; (4) Taken together, it shows that company size, asset structure and profitability simultaneously affect the capital structure of pharmaceutical companies listed on the Indonesia Stock Exchange for the 2016-2020 period. Limitation:This research was only conducted on the variables of company size, asset structure and profitability including: ROA, ROE and NPM as well as the capital structure of pharmaceutical companies listed on the Indonesia Stock Exchange for the 2016-2020 period. Impact: Provides an overview of the company related to company size, asset structure, profitability have a significant effect on capital structure. Keywords:Firm Size, Asset Structure, ROA, NPM, ROE, Capital Structure